Precarity and the pandemic: an inquiry into the impact of Covid19 on the working lives of non-permanent educators in post-compulsory education in Ireland. Issue 4 (2nd October 2022) - Fitzsimons, Camilla; Henry, Sean; O'Neill, Jerry
ABSTRACT: The paper analyses how educators employed on non-permanent contracts in the non-compulsory education sector in Ireland have fared during the Covid 19 pandemic. These employees were starting from a low base in relation to the terms and conditions of their employment when their places of work dramatically pivoted online in March 2020. We argue the impacts of the pandemic were disproportionate, with people reporting such things as increased workloads, exclusion from HR update communications and little supports in creating workspaces in their homes. In this sense, we foreground how participants' places of work often assumed that all employees, precarious and permanent, had the same level of access to resources.Furthermore, given the gendered nature of caring responsibilities and the high proportion of women respondents in the research, we highlight the extent to which the pandemic increased caring responsibilities and impacted on female participants' capacity to work. Overall, we demonstrate how the Covid 19 pandemic hasn't, in itself, created unsatisfactory working conditions, rather, it has both exposed and accentuated existing shortfalls and further proved, if such proof was needed, that short-term actions compound the many problems with precarity in post-compulsory education work.